Hubungan Regulasi Diri dengan Fear of Missing Out (FoMO) pada Mahasiswa - Alfanny Maulany Yusra; Lisfarika Napitupulu (Journal of Islamic and Contemporary Psychology (JICOP), 2022)
Social media at this time is no longer a tool to find information, but provides an opportunity for each individual to find out more valuable activities carried out by others compared to the experience they have. Therefore, it causes anxiety and fear when people can't connect with activities that other people do on social media and in everyday life which is called Fear of Missing Out (FoMO). FOMO happen to adult including final year-students. The purpose of this study was to determine whether there is a relationship between self-regulation and Fear of Missing Out (FoMO) in final year students at the Islamic University of Riau. As many as, 118 last year students were taken for research samples using the Convenience Sampling technique. Correlation analysis shows that there is a negative relationship between Self-Regulation and Fear Of Missing Out (FoMO) (r) = -373 with p value = .000 (p < .05), which means that the higher the Self-Regulation, the lower the Fear Of Missing Out (FoMO). On the other hand, the lower the Self-Regulation, the higher the Fear Of Missing Out (FoMO) experienced by final year students.